2010
DOI: 10.1177/0003319710371614
|View full text |Cite
|
Sign up to set email alerts
|

Study on Unrecognized Peripheral Arterial Disease (PAD) by Ankle/Brachial Index and Arterial Comorbidity in Catania, Sicily, Italy

Abstract: Peripheral arterial disease (PAD) is under diagnosed and early diagnosis decreases consequences. We screened unrecognized PAD focusing on arterial co-morbidities. In the 3412 subjects, screened from 10 general practices in the city of Catania (Sicily, Italy), ankle brachial index (ABI) measurements were performed. An ABI < or =0.9 was considered as valid in diagnosing PAD. ABI value < or =0.9 was found in 2.3%, and a significant rate of carotid stenosis was also found Echocardiographic markers left ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Ward et al [18] in the study of 204 patients with symptomatic PAD found that LVEF less than 55% among patients with low ABI is more common than normal ABI. Also in the study by Santo Signorelli et al [19] LVEF < 50% had higher prevalence in patients with ABI ≤ 0.9. Unlike these findings, Thatipelli et al [20] studied 395 patients referred for dobutamin stress echocardiography and ABI determination, and observed that there was no relation between ABI and left ventricle wall motion index score at rest or after stress.…”
Section: Discussionmentioning
confidence: 78%
“…Ward et al [18] in the study of 204 patients with symptomatic PAD found that LVEF less than 55% among patients with low ABI is more common than normal ABI. Also in the study by Santo Signorelli et al [19] LVEF < 50% had higher prevalence in patients with ABI ≤ 0.9. Unlike these findings, Thatipelli et al [20] studied 395 patients referred for dobutamin stress echocardiography and ABI determination, and observed that there was no relation between ABI and left ventricle wall motion index score at rest or after stress.…”
Section: Discussionmentioning
confidence: 78%
“…Since then, several groups have confirmed this relationship in different cohorts including elderly patients with ischemic heart disease, diabetics and nondiabetics, and in subjects with atrial fibrillation [8,9,10,11,12]. In addition, few earlier studies reported a relation between LVEF and ABI as a secondary finding [13,14,15].…”
Section: Introductionmentioning
confidence: 88%
“…However, a limited number of studies have focused on N in severe peripheral arterial disease (PAD) such as critical limb ischemia (21), whereas no study has focused on chronic PAD. PAD is considered a marker of the extent of the atheromatous process and it is known that PAD patients have a high risk of mortality for ischemic events (22)(23)(24)(25). The present study focused on N plasma levels in symptomatic (SyP) and asymptomatic (AsP) PAD patients and compared them to the controls.…”
Section: Introductionmentioning
confidence: 99%